A study on the effect of different led lighting on the growth of green onion (Allium Fistulosum) - Lean, Chyng Yee (2021)
Urbanisation has reduced land for agricultural purposes. Greenhouse or vertical farming system is a more space-, cost- and time-saving method to grow greens. Plants were grown under natural lighting conventionally. The present study focuses on growth of plants under Light Emitting Diodes (LED) lighting which may potentially overcome the problems encountered by the traditional method. The aim of this research is to provide a conducive yet more efficient environment for the development of plants. By conducting this research, the best and most efficient LED colour for planting greens and optimal duration of light exposure to the plants in a greenhouse can be known. Green onions (Allium fistulosum) were grown under mixture of red and blue LEDs, solely red LEDs and only blue LEDs. An additional control set where green onions were exposed to sunlight was performed to allow comparison of result. Responding variables were the number of leaves, height and weight of plant. Green onions under the light influence of blue LEDs lead in all the parameters concerned. Furthermore, green onions exposed to lights for 12 h have a more positive result than those exposed for 6 h. Thus, green onions are best to be cultivated in blue LEDs for 12 h.